Clay exfoliation and polymer/clay aerogels by supercritical carbon dioxide - Longo, Simona; Mauro, Marco; Daniel, Christophe; Galimberti, Maurizio; Guerra, Gaetano (Frontiers in Chemistry, 2013)
Supercritical carbon dioxide (scCO2) treatments of a montmorillonite (MMT) intercalated with ammonium cations bearing two long hydrocarbon tails (organo-modified MMT, OMMT) led to OMMT exfoliation, with loss of the long-range order in the packing of the hydrocarbon tails and maintenance of the long-range order in the clay layers. The intercalated and the derived exfoliated OMMT have been deeply characterized, mainly by X-ray diffraction analyses. Monolithic composite aerogels, with large amounts of both intercalated and exfoliated OMMT and including the nanoporous-crystalline δ form of syndiotactic polystyrene (s-PS), have been prepared, by scCO2 extractions of s-PS-based gels. Also for high OMMT content, the gel and aerogel preparation procedures occur without re-aggregation of the exfoliated clay, which is instead observed for other kinds of polymer processing. Aerogels with the exfoliated OMMT have more even dispersion of the clay layers, higher elastic modulus and larger surface area than aerogels with the intercalated OMMT. Extremely light materials with relevant transport properties could be prepared. Moreover, s-PS-based aerogels with exfoliated OMMT could be helpful for the handling of exfoliated clay minerals.